The influence of different drying methods on the quality attributes of beetroots - Liu, Yan; Sabadash, Sergei; Duan, Zhenhua; Deng, Chunli (Eastern-European Journal of Enterprise Technologies, 2022)
Beetroot is recognized as a health-promoting vegetable due to its abundant source of bioactive compounds. Drying methods significantly influence the quality of products. Therefore, it is important to choose a suitable drying method to obtain high quality of dried beetroots. The aim of this research was to investigate the influence of different drying methods on the quality attributes of beetroots. Fresh beetroots were dehydrated by freeze drying (FD), heat pump drying (HPD), vacuum drying (VD), microwave drying (MD) and microwave vacuum drying (MVD), respectively. The drying time, final moisture content, rehydration ratio, color, microstructure, betalain content and total flavonoids content of beetroots prepared by different drying methods were analyzed. The results showed that MVD and MD were superior to VD, HPD and FD in terms of drying time. The drying time (0.77±0.03 h) of MD was reduced by 97.40 % compared with FD, which was only 9.83 % of VD and 11.27 % of HPD. No significant differences in the final moisture content among beetroots dried using different drying methods were observed. Beetroots dried by FD showed the most desirable color and porous structure. Besides, beetroots dried by MVD exhibited the largest rehydration ratio, while the lowest rehydration ratio appeared in the beetroots obtained using MD. In addition, beetroots prepared by HPD illustrated the highest contents of betacyanin, betaxanthin and total flavonoids, which were 5.48±0.03 mg/g, 2.40±0.02 mg/g and 24.71±0.47 mg rutin equivalent/g, respectively. These results identify that it is difficult to achieve the best quality dried beetroots using a single drying method. Therefore, considering the quality attributes, the combined drying method (HPD+MVD) would be a very promising alternative method for obtaining dehydrated beetroots